2022
DOI: 10.1111/pbi.13973
|View full text |Cite
|
Sign up to set email alerts
|

Meliaceae genomes provide insights into wood development and limonoids biosynthesis

Abstract: Summary Meliaceae is a useful plant family owing to its high‐quality timber and its many limonoids that have pharmacological and biological activities. Although some genomes of Meliaceae species have been reported, many questions regarding their unique family features, namely wood quality and natural products, have not been answered. In this study, we provide the whole‐genome sequence of Melia azedarach comprising 237.16 Mb with a contig N50 of 8.07 Mb, and an improved genome sequence of Azadirachta indica com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The genome sequences of Melia azedarach , Azadirachta indica and Toona sinensis (also called Chinese mahogany) from the Meliaceae family have been compared. The results show the genes related to cellulose and hemicellulose biosynthesis, as well as their corresponding regulatory transcription factors, are significantly expanded in Toona sinensis (Cui et al, 2023). Ochroma pyramidale , also known as balsa, is a fast‐growing tree the wood of which is soft and light, while Mesua ferrea , often called ironwood, generates wood with a high density and hardness.…”
Section: Understanding Of Wood Formationmentioning
confidence: 99%
“…The genome sequences of Melia azedarach , Azadirachta indica and Toona sinensis (also called Chinese mahogany) from the Meliaceae family have been compared. The results show the genes related to cellulose and hemicellulose biosynthesis, as well as their corresponding regulatory transcription factors, are significantly expanded in Toona sinensis (Cui et al, 2023). Ochroma pyramidale , also known as balsa, is a fast‐growing tree the wood of which is soft and light, while Mesua ferrea , often called ironwood, generates wood with a high density and hardness.…”
Section: Understanding Of Wood Formationmentioning
confidence: 99%
“…Year 2012 [8] 2015 [112] 2016 [9] 2022 [16] 2022 [15] 2022 [15] Tissue Root, leaf, pathway from 2,3-epoxidized squalene to azadirachtin A. It was suggested that 2,3-epoxidized squalene initially forms a Euphorbia dienol intermediate under enzymatic catalysis, followed by a series of reactions leading to the production of azadirachtin A.…”
Section: Azadirachta Indica a Indica A Indica A Indica A Indica Melia...mentioning
confidence: 99%
“…However, this inference was deemed inconclusive at the time [115] . Subsequently, the abundant azadirachtin genome and transcriptome information available to the public was analyzed, including the complementary DNA (cDNA) library [7] , draft genome [8][9] , EST libraries [10][11] , transcriptome data [8,[12][13][14] , and chromosome-level genome data [15][16] . This search encompassed genes from the MVA pathway, MEP pathway, 2,3-oxosqualene synthesis, and cytochrome P450 (CYP450s).…”
Section: Azadirachta Indica a Indica A Indica A Indica A Indica Melia...mentioning
confidence: 99%
See 2 more Smart Citations